Luther's Influence on Calvin's political Transformation - Chandra, Tjahyadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The significance of John Calvin for modern times is clearly expressed in these words: "The sixteenth century was an extraordinary century”. Of all the people who made this century great, only Calvin has made broad contributions to the wider country. Calvinism is the name given to the system of thought that was revealed to us by John Calvin. He is recognized as the main initiator of this system, even though he is not the creator of the ideas contained in it. Calvin's theological views, along with other great leaders of the Protestant Reformation (Augustine and Martin Luther), are known as the rise of Augustinianism, which in turn is the same as the revival of the teachings of the Apostle Paul. But it was Calvin who first presented the basics of this view for modern times, in the systematic form and with the special application that we know from his time as Calvinism. Calvinism does not limit itself to theology; Calvinism is a comprehensive system of thought, which includes views on politics, society, science, and art, in addition to theology. A Calvinist tries to apply the truth of the Scriptures. Calvinism does not stop at the church structure, but extends within one system of life, and Calvinism elevates Christianity to the highest spiritual beauty; Calvinism created the church structure, which was a prerequisite for the confederate state; Calvinism developed a political scheme, which gave birth to constitutional government, both in Europe and in America; Calvinism promotes holiness through high moral standards in our social environment. Calvinism places under Church and State, under society and household circles, a strict philosophical conception. This dissertation is written in a qualitative method, "analyzing the data collected in the study, the main findings resulting from the data analysis". Qualitative research usually uses descriptive methods such as observation, data study, using data that can be analyzed through data or literature studies. This dissertation is written from the background of John Calvin's life, his conversion, even since he was a child, Calvin was happy to study law. The author explains the historical context of the institute, as well as the influence of the concept of civil government from Augustine (City of God) and Martin Luther (Two Kingdoms); the explanation is continued with the concept of civil government according to John Calvin, through the principles of government, also explains Calvin's ideas in relation to theocracy.